Gray Matter Atrophy Associated with Extrapyramidal Signs in the Lewy Body Variant of Alzheimer’s Disease - Choi, Seong Hye (2012)
Up to 60% of the patients with Alzheimer’s disease (AD) can have cortical or brainstem Lewy bodies (LB), and extrapyramidal signs (EPS) have been found to be associated with LB in AD patients. However, the relationship between EPS and brain volumes has not been studied in the LB variant of AD using structural magnetic resonance imaging (MRI). The purpose of this study was to determine the relationship between patterns of brain atrophy and clinical EPS in patients with pathologically confirmed AD. We compared gray matter structure using voxel-based morphometry in 29 Definite AD cases, 16 (55%) of whom also had LBs identified with α-synuclein immunohistochemistry. Multivariate models analyzed brain volume at a voxel level accounting for subject group, Mini-Mental State Examination (MMSE), EPS, total brain volume, and the time from MRI scan to death. There was no significant difference in gray matter volume in the Definite AD patients as a function of LB. There was a significant association between gray matter volumes and the MMSE in AD patients, both with and without LBs. There was a significant correlation between gray matter volume and EPS only in the group of AD patients with LBs, and not in those with pure AD. These findings suggest that that the etiology of EPS in patients with the LB variant of AD is associated with neuronal loss in the nigrostriatal tracts. By contrast, the source of the EPS in AD alone appears to be less well localized.